Age and sex differences in soluble ACE2 may give insights for COVID-19 - Swärd, Per; Edsfeldt, Andreas; Reepalu, Anton; Jehpsson, Lars; Rosengren, Björn E.; Karlsson, Magnus K. (Critical care (London, England), 2020)
SEE PDF] There was similar and low sACE2 in both sexes up to age 12. sACE2 increased more in boys with growth, so men from age 15 had higher sACE2 than women (Fig. 1). [...]sACE2 is low in children and increases more in boys than girls, resulting in sex differences in adolescence/young adulthood. High mACE2 and/or high ADAM-17 activity may therefore be risk factors for severe COVID-19 [1, 2]. Since high sACE2 could indicate high mACE2 and/or high ADAM-17 activity, sACE2 may be a marker of both susceptibility and severity of COVID-19. [...]this study shows that subjects with higher risk for severe COVID-19 [4] had higher sACE2 (adults>children and men>women).